FEMALE GENITAL ABNORMALITIES - Gutiérrez, Carlos (2015)
A study of 58 patients was performed with abnormalities of the genital tract, seen between 1970 and 1984. one case per 555 hospitalized women was recorded. The most common genital abnormalities were vaginal septum (25.9%), imporforado hymen (17.2%), vaginal agenesis (12%) and Gartner cyst (12%). It was also found agenesis uterine (8.8%), uterus bicorne (6.9%), didelphic uterus (5.2%), uterine hypoplasia (5.2%), partitioning (1.7%) uterus hypertrophy cervix (1.7%), Rokitansky syndrome (1.7%) and pseudohermaphroditism (1.7%). As diagnostic procedures laparotomy, laparoscopy, neumopelvigrafías, ultrasound, excretory urography, hysterosalpingography, urethrogram, vaginography, and studies sexual chromatin was made. Surgical treatment was performed in 44 cases. The postoperative complications were vaginal stenosis (2 cases), vaginal bleeding (2 cases), and abdominal hernia (1 case).